GENETIC ANALYSIS AND INTERRELATIONSHIP OF YIELD ATTRIBUTING TRAITS IN CHICKPEA ( C icer arietinum L.) - R. Gul; H. Khan; M. Bibi; Q. U. Ain; B. Imran (Journal of Animal and Plant Sciences, 2013)
Twenty chickpea (Cicer arietinum L.) genotypes were evaluated for genetic potential, heritability, genetic advance and traits association of yield contributing characters during 2010-2011, at The University of Agriculture, Peshawar. The experiment was carried out in a randomized complete block (RCB) design with three replications. Data were recorded on days to 50% flowering, pods per plant, seeds per pod, number of primary branches plant-1 , number of secondary branches plant-1 , 100-seed weight and seed yield plant-1 . Analysis of variance revealed significant (P<0.01) variation among genotypes for all the studied characters. Broad sense heritability estimates were highest for pods per plant (0.88), primary branches plant-1 (0.83), 100-seed weight (0.82), seed yield plant-1 (0.75) and secondary branches plant-1 (0.77). Genetic advance was higher for pods per plant (40.14), seed yield plant -1 (38.24%), primary branches plant-1 (36.64%) and secondary branches plant-1 (30.25%). Seed yield plant-1 showed highly significant genetic as well as phenotypic correlation with pods per plant, number of primary branches plant-1 , secondary branches plant-1 and 100-seed weight in positive direction. To conclude, pods per plant, number of primary branches, number of secondary branches and 100- seed weight would be the appropriate selection criteria for better seed yield in chickpea.
Keywords: Chickpea; genetic analysis; interrelationship; yield; traits